2013
DOI: 10.1186/1471-2334-13-424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ganciclovir for the treatment of severe cytomegalovirus-associated pneumonia in children without a specific immunocompromised state

Abstract: BackgroundThis study aimed to evaluate the effectiveness of gancyclovir (GCV) treatment for severe cytomegalovirus (CMV)-associated pneumonia in immunocompetent children.MethodWe enrolled patients with CMV-associated severe pneumonia admitted to the Vietnam National Hospital of Pediatrics, Hanoi, Vietnam, from January 2010 to December 2011. On admission, though respiratory bacteria and viruses were not detected in tracheal aspirates, more than 5 × 103 copies/mL of CMV-DNA were detected in both tracheal aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Thanh Thi Mai Doan et al . investigated 43 patients with CMV‐associated severe pneumonia and showed that the median CMV viral load in plasma was 59·5 × 10 3 copies/mL, whereas that in tracheal aspirate specimens was 120 × 10 3 copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Thanh Thi Mai Doan et al . investigated 43 patients with CMV‐associated severe pneumonia and showed that the median CMV viral load in plasma was 59·5 × 10 3 copies/mL, whereas that in tracheal aspirate specimens was 120 × 10 3 copies/mL.…”
Section: Resultsmentioning
confidence: 99%
“…A third were premature, a risk group known to have impaired Tcell and immunoglobulin response to CMV infection [17][18][19]. The association between NEC and CMV in this group is unclear, as CMV could be secondarily reactivated by the inflammation; however, in HIV positive infants younger than 3 months, an NEC-like presentation with multiple 'punched-out' perforations throughout the small bowel is a distinctive presentation which should prompt CMV work-up, and may represent primary CMV enteritis [20].…”
Section: Clinical Presentation and Risk Factorsmentioning
confidence: 99%
“…Although clear data about the duration of anti-CMV therapy in immunocompetent individuals are not present, there are various studies about treatment regimens ranging between 5 and 21 days (2,9,14,15), and even more long-term applications in some cases based on clinical and laboratory findings are present (17,18). Ganciclovir treatment was administered to our patients in the appropriate period specified in the literature.…”
Section: Discussionmentioning
confidence: 99%